Cinta Situregen: Mengatasi Abrasi dan Sampah di Desa Situregen - Ulum, Reza Miftahul; Fahreza Y H, M Ryan; Juliana, Aisyah; Fathonah , Ainnun; Widyawati; Malika, Illinia; Prayogi, Khalfi; Andika, Dicky; Taryono (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
KKNT IPB Innovation 2024 is a community service program that integrates higher education curricula to train students in analyzing and finding solutions to societal problems. Situregen Village has the potential for tourism, particularly the Cimandiri Beach, but faces issues with coastal cleanliness. This community service activity aims to implement innovation through the planting of abrasion-preventing plants such as mangroves, sea pandanus, and sea pines, as well as waste management practices. The program involves various local communities and institutions, including the Beach and Sea Lovers Community (KPPL) and the Disaster-Resilient Village (Destana), in activities such as socialization, planting, and beach cleaning to reduce the negative impacts of environmental pollution and improve aesthetics and public health. The activities include socializing waste segregation and practical actions like planting and beach cleaning on different dates. The results show positive impacts in reducing abrasion, increasing environmental awareness, and building active community participation. Challenges faced include suboptimal participation and miscommunication between parties. Sustainability recommendations include periodic education, continuous planting, and the establishment of local working groups to monitor the program. This program demonstrates that with active involvement from various stakeholders and the community, Situregen Village can become a model for a clean, healthy, and sustainable village.